2016
DOI: 10.1111/hdi.12407
|View full text |Cite
|
Sign up to set email alerts
|

The greatly misunderstood erythropoietin resistance index and the case for a new responsiveness measure

Abstract: Background The optimal use of erythropoiesis stimulating agents (ESAs) to treat anemia in end stage renal disease (ESRD) remains controversial due to reported associations with adverse events. In analyzing these associations, studies often utilize ESA resistance indices (ERIs), to characterize a patient’s response to ESA. In this study, we examine whether ERI is an adequate measure of ESA resistance. Methods We used retrospective data from a non-concurrent cohort study of incident hemodialysis patients in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 34 publications
0
29
0
Order By: Relevance
“…Nonetheless, meal analysis is necessary to confirm this when conducting a similar study. Fourth, as Chait et al reported, as an index, ERI is similar to weight‐ and non‐weight‐adjusted EPO . In the existing guidelines, ERI is not identified as associated with prognosis.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Nonetheless, meal analysis is necessary to confirm this when conducting a similar study. Fourth, as Chait et al reported, as an index, ERI is similar to weight‐ and non‐weight‐adjusted EPO . In the existing guidelines, ERI is not identified as associated with prognosis.…”
Section: Discussionmentioning
confidence: 95%
“…Fourth, as Chait et al reported, as an index, ERI is similar to weight-and non-weight-adjusted EPO. 24 In the existing guidelines, ERI is not identified as associated with prognosis. ERI should be defined in terms of the results of prospective trials in which its association with prognosis was evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…It has become routine for studies to report ERI as a measure of ESA dose requirements. A recent study found that a strong linear relationship exists between ERI and weight-adjusted ESA dose using a universal formula [ 13 ]. However, it is important to take cognisance of the timing of the ESA initiation and the value of the accompanying Hb concentration when calculating the ERI.…”
Section: Introductionmentioning
confidence: 99%
“…ERI is a complex metric representing the responsiveness to the treatment of anemia. 29 Patients with higher ERIs are less responsive to the drug effect. In the PD model, SC 50 reflects the sensitivity of HGB response to the drug effect.…”
Section: Discussionmentioning
confidence: 99%